ANALISIS PENGARUH QUICK RATIO TERHADAP RETURN ON ASSET PADA CV. PARULIAN SOJUANGON PANGGABEAN KABUPATEN TAPANULI TENGAH - Yolamandasari; Nasution, Zafril Abdi; Koto, Mhd. Shafwan (Jurnal Riset Rumpun Ilmu Ekonomi, 2023)
This study aims to examine the effect of the quick ratio on return on assets at CV. Parulian Sojuangon Panggabean Group, Central Tapanuli Regency. The author uses research methods in quantitative descriptive to discuss the problems faced by corporate finance. Data analysis explained the use of the results of several linear sub-data analyzes regarding the quick ratio (current ratio) to return on assets (Y). The results showed that there was a negative relationship between the quick ratio and return on equity on CV. Parulian Sojuangon Panggabean Group Central Tapaanuli Regency is 0.333, so when interpreted on a value scale it can be categorized as low. The regression equation obtained Y = 0.500 - 0.206X which shows the effect of the quick ratio on return on assets on CV. Parulian Sojuangon Panggabean Group, Central Tapanuli Regency. The t test shows that the hypothesis proposed is rejected (not significant), where t count is 0.612 > 3.18245, which means that return on assets is not necessarily reduced by the regression coefficient/slop (0.206) if the quick ratio variable is added by one unit. While the coefficient of determination is known that the quick ratio only plays a role of 11.1% of the return on assets at CV. Parulian Sojuangon Panggabean Group Central Tapanuli Regency and the remaining 88.9% is influenced by other factors not included in the model.